Safe Haskell  None 

Language  Haskell2010 
Synopsis
 newtype ScopeT b t f a = ScopeT {}
 (>>>>=) :: (Monad f, Functor (t f)) => ScopeT b t f a > (a > f c) > ScopeT b t f c
 abstractT :: (Functor (t f), Monad f) => (a > Maybe b) > t f a > ScopeT b t f a
 abstract1T :: (Functor (t f), Monad f, Eq a) => a > t f a > ScopeT () t f a
 abstractTEither :: (Functor (t f), Monad f) => (a > Either b c) > t f a > ScopeT b t f c
 abstractTName :: (Functor (t f), Monad f) => (a > Maybe b) > t f a > ScopeT (Name a b) t f a
 abstract1TName :: (Functor (t f), Monad f, Eq a) => a > t f a > ScopeT (Name a ()) t f a
 instantiateT :: (Bound t, Monad f) => (b > f a) > ScopeT b t f a > t f a
 instantiate1T :: (Bound t, Monad f) => f a > ScopeT b t f a > t f a
 instantiateTEither :: (Bound t, Monad f) => (Either b a > f c) > ScopeT b t f a > t f c
 fromScopeT :: (Bound t, Monad f) => ScopeT b t f a > t f (Var b a)
 toScopeT :: (Functor (t f), Monad f) => t f (Var b a) > ScopeT b t f a
 lowerScopeT :: (Functor (t f), Functor f) => (forall x. t f x > g x) > (forall x. f x > g x) > ScopeT b t f a > Scope b g a
 splatT :: (Bound t, Monad f) => (a > f c) > (b > f c) > ScopeT b t f a > t f c
 bindingsT :: Foldable (t f) => ScopeT b t f a > [b]
 mapBoundT :: Functor (t f) => (b > b') > ScopeT b t f a > ScopeT b' t f a
 mapScopeT :: (Functor (t f), Functor f) => (b > d) > (a > c) > ScopeT b t f a > ScopeT d t f c
 foldMapBoundT :: (Foldable (t f), Monoid r) => (b > r) > ScopeT b t f a > r
 foldMapScopeT :: (Foldable f, Foldable (t f), Monoid r) => (b > r) > (a > r) > ScopeT b t f a > r
 traverseBoundT_ :: (Applicative g, Foldable (t f)) => (b > g d) > ScopeT b t f a > g ()
 traverseScopeT_ :: (Applicative g, Foldable f, Foldable (t f)) => (b > g d) > (a > g c) > ScopeT b t f a > g ()
 traverseBoundT :: (Applicative g, Traversable (t f)) => (b > g c) > ScopeT b t f a > g (ScopeT c t f a)
 traverseScopeT :: (Applicative g, Traversable f, Traversable (t f)) => (b > g d) > (a > g c) > ScopeT b t f a > g (ScopeT d t f c)
 bitransverseScopeT :: Applicative f => (forall x x'. (x > f x') > t s x > f (t' s' x')) > (forall x x'. (x > f x') > s x > f (s' x')) > (a > f a') > ScopeT b t s a > f (ScopeT b t' s' a')
Documentation
newtype ScopeT b t f a Source #
is a Scope
b f at f
expression abstracted over f
,
with bound variables in b
, and free variables in a
.
Scope
n f a ~ScopeT
nIdentityT
f aScopeT
n t f a ~ t (Scope
n f) a
Instances
(Functor (t f), Functor f) => Functor (ScopeT b t f) Source #  
(Foldable (t f), Foldable f) => Foldable (ScopeT b t f) Source #  
Defined in Bound.ScopeT fold :: Monoid m => ScopeT b t f m > m # foldMap :: Monoid m => (a > m) > ScopeT b t f a > m # foldr :: (a > b0 > b0) > b0 > ScopeT b t f a > b0 # foldr' :: (a > b0 > b0) > b0 > ScopeT b t f a > b0 # foldl :: (b0 > a > b0) > b0 > ScopeT b t f a > b0 # foldl' :: (b0 > a > b0) > b0 > ScopeT b t f a > b0 # foldr1 :: (a > a > a) > ScopeT b t f a > a # foldl1 :: (a > a > a) > ScopeT b t f a > a # toList :: ScopeT b t f a > [a] # null :: ScopeT b t f a > Bool # length :: ScopeT b t f a > Int # elem :: Eq a => a > ScopeT b t f a > Bool # maximum :: Ord a => ScopeT b t f a > a # minimum :: Ord a => ScopeT b t f a > a #  
(Traversable (t f), Traversable f) => Traversable (ScopeT b t f) Source #  
Defined in Bound.ScopeT  
(Monad f, Bound t, Eq b, Eq1 (t f), Eq1 f) => Eq1 (ScopeT b t f) Source #  
(Monad f, Bound t, Ord b, Ord1 (t f), Ord1 f) => Ord1 (ScopeT b t f) Source #  
Defined in Bound.ScopeT  
(Read b, Read1 (t f), Read1 f) => Read1 (ScopeT b t f) Source #  
Defined in Bound.ScopeT liftReadsPrec :: (Int > ReadS a) > ReadS [a] > Int > ReadS (ScopeT b t f a) # liftReadList :: (Int > ReadS a) > ReadS [a] > ReadS [ScopeT b t f a] # liftReadPrec :: ReadPrec a > ReadPrec [a] > ReadPrec (ScopeT b t f a) # liftReadListPrec :: ReadPrec a > ReadPrec [a] > ReadPrec [ScopeT b t f a] #  
(Show b, Show1 (t f), Show1 f) => Show1 (ScopeT b t f) Source #  
(Hashable b, Bound t, Monad f, Hashable1 f, Hashable1 (t f)) => Hashable1 (ScopeT b t f) Source #  
Defined in Bound.ScopeT  
(Monad f, Functor (t f)) => Module (ScopeT b t f) f Source #  
(Monad f, Bound t, Eq b, Eq1 (t f), Eq1 f, Eq a) => Eq (ScopeT b t f a) Source #  
(Monad f, Bound t, Ord b, Ord1 (t f), Ord1 f, Ord a) => Ord (ScopeT b t f a) Source #  
Defined in Bound.ScopeT compare :: ScopeT b t f a > ScopeT b t f a > Ordering # (<) :: ScopeT b t f a > ScopeT b t f a > Bool # (<=) :: ScopeT b t f a > ScopeT b t f a > Bool # (>) :: ScopeT b t f a > ScopeT b t f a > Bool # (>=) :: ScopeT b t f a > ScopeT b t f a > Bool #  
(Read b, Read1 (t f), Read1 f, Read a) => Read (ScopeT b t f a) Source #  
(Show b, Show1 (t f), Show1 f, Show a) => Show (ScopeT b t f a) Source #  
NFData (t f (Var b (f a))) => NFData (ScopeT b t f a) Source #  
Defined in Bound.ScopeT  
(Hashable b, Bound t, Monad f, Hashable1 f, Hashable1 (t f), Hashable a) => Hashable (ScopeT b t f a) Source #  
Defined in Bound.ScopeT 
Abstraction
abstractT :: (Functor (t f), Monad f) => (a > Maybe b) > t f a > ScopeT b t f a Source #
Capture some free variables in an expression to yield a ScopeT
with bound variables in b
.
abstract1T :: (Functor (t f), Monad f, Eq a) => a > t f a > ScopeT () t f a Source #
Abstract over a single variable.
>>>
abstract1T 'x' (MaybeT (Nothing : map Just "xyz"))
ScopeT (MaybeT [Nothing,Just (B ()),Just (F "y"),Just (F "z")])
abstractTEither :: (Functor (t f), Monad f) => (a > Either b c) > t f a > ScopeT b t f c Source #
Capture some free variables in an expression to yield a ScopeT
with bound variables in b
. Optionally change the types of the remaining free variables.
Name
abstractTName :: (Functor (t f), Monad f) => (a > Maybe b) > t f a > ScopeT (Name a b) t f a Source #
Abstraction, capturing named bound variables.
abstract1TName :: (Functor (t f), Monad f, Eq a) => a > t f a > ScopeT (Name a ()) t f a Source #
Abstract over a single variable
Instantiation
instantiateT :: (Bound t, Monad f) => (b > f a) > ScopeT b t f a > t f a Source #
Enter a ScopeT
, instantiating all bound variables
instantiate1T :: (Bound t, Monad f) => f a > ScopeT b t f a > t f a Source #
Enter a ScopeT
that binds one variable, instantiating it
instantiateTEither :: (Bound t, Monad f) => (Either b a > f c) > ScopeT b t f a > t f c Source #
Enter a ScopeT
, and instantiate all bound and free variables in one go.
Traditional de Bruijn
fromScopeT :: (Bound t, Monad f) => ScopeT b t f a > t f (Var b a) Source #
Convert to traditional de Bruijn.
toScopeT :: (Functor (t f), Monad f) => t f (Var b a) > ScopeT b t f a Source #
Convert from traditional de Bruijn to generalized de Bruijn indices.
Bound variable manipulation
lowerScopeT :: (Functor (t f), Functor f) => (forall x. t f x > g x) > (forall x. f x > g x) > ScopeT b t f a > Scope b g a Source #
Convert to Scope
.
splatT :: (Bound t, Monad f) => (a > f c) > (b > f c) > ScopeT b t f a > t f c Source #
Perform substitution on both bound and free variables in a ScopeT
.
bindingsT :: Foldable (t f) => ScopeT b t f a > [b] Source #
Return a list of occurences of the variables bound by this ScopeT
.
mapBoundT :: Functor (t f) => (b > b') > ScopeT b t f a > ScopeT b' t f a Source #
Perform a change of variables on bound variables.
mapScopeT :: (Functor (t f), Functor f) => (b > d) > (a > c) > ScopeT b t f a > ScopeT d t f c Source #
Perform a change of variables, reassigning both bound and free variables.
foldMapBoundT :: (Foldable (t f), Monoid r) => (b > r) > ScopeT b t f a > r Source #
Obtain a result by collecting information from bound variables
foldMapScopeT :: (Foldable f, Foldable (t f), Monoid r) => (b > r) > (a > r) > ScopeT b t f a > r Source #
Obtain a result by collecting information from both bound and free variables
traverseBoundT_ :: (Applicative g, Foldable (t f)) => (b > g d) > ScopeT b t f a > g () Source #
traverseScopeT_ :: (Applicative g, Foldable f, Foldable (t f)) => (b > g d) > (a > g c) > ScopeT b t f a > g () Source #
traverse_
both the variables bound by this scope and any free variables.
traverseBoundT :: (Applicative g, Traversable (t f)) => (b > g c) > ScopeT b t f a > g (ScopeT c t f a) Source #
traverseScopeT :: (Applicative g, Traversable f, Traversable (t f)) => (b > g d) > (a > g c) > ScopeT b t f a > g (ScopeT d t f c) Source #
traverse
both bound and free variables
:: Applicative f  
=> (forall x x'. (x > f x') > t s x > f (t' s' x')) 

> (forall x x'. (x > f x') > s x > f (s' x')) 

> (a > f a')  
> ScopeT b t s a  
> f (ScopeT b t' s' a') 
If you are looking for bitraverseScopeT
, this is the monster you need.